Menyingkap Fenomena Tax Amnesty Di Indonesia: Sebuah Analisis Dengan Pendekatan Luder’s Contingency Model - Novitasari, Susan (AKTSAR: Jurnal Akuntansi Syariah, 2018)
Tax amnesty is one of Indonesia’s Government policy to increase the state revenues, especially in the taxation sector. The main purpose of tax amnesty is repatriation and increase the tax database. The objectives of the research are (1) to know the stimulus of tax amnesty policy in Indonesia, the provider and user of tax amnesty policy information, and implementation barriers; (2) To know the strategy that still must be implemented by DJP after tax amnesty. This research is qualitative with critical thinking analysis using Luder's Contingency Model. In depth interviews with the officials of DJP is used as an instrument of data collection, complemented by secondary data and literature studies. The results show that there are three stimulus that led to the implementation of tax amnesty, the parties associated with tax amnesty, and implementation barriers. The study also highlighted the condition after tax amnesty, especially those applied to tax evaders who did not participate in tax amnesty. From the barriers that have been analyzed, the Government can provide stimulus by innovating the improvements or making policy on the strategy after the tax amnesty, so that it can provide benefits to improve and continue the struggle of tax amnesty which actually has not ended.